Peculiarities of yield formation of tomato in the protected ground of the Udmurt Republic - T. N. Tutova; E. V. Sokolova; L. A. Nesmelova; T. E. Ivanova (Овощи России, 2020)
Relevance. A large reserve to increase the production of tomatoes for different periods of cultivation and purposes of use are highly productive new varieties and heterotic hybrids. In this regard, one of the important conditions now is the maximum compliance of newly created varieties and hybrids with modern technologies that allow obtaining competitive products. In addition to the main indicators (high yield, early maturity, favorable maturation), varietal features such as transportability of fruits,high taste appeal (especially salad-type hybrids), appearance, resistance to major diseases and manufacturability are also important. In recent years, tomato and other vegetable crops have grown mainly hybrids of the first generation F1 and line (the result of targeted selection), less often populations. For more than a decade, only hybrid varieties have been grown in industrial greenhouse vegetable production.Methods. The article presents the results of 7-year research on the yield, its structure and quality of fruits of indeterminate tomato hybrids. Research on the yield and quality of fruits of indeterminate tomato hybrids was carried out in 2011-2017, in JSC "Zavyalovsky Greenhouse plant" of the Udmurt Republic.Results. Hybrid F1 tomato Ismail, F1 Macarena, F1 Mace, F1 Geronimo and F1 Starbuck were distinguished by high productivity. This indicator was respectively: 34.5 kg / m2; 33.1 kg / m2; 32.3 kg / m2; 32.0 kg / m2 and 31.2 kg / m2. Tomatoes F1 Yakimanka, F1 Foronti, F1 Starbuck, F1 Taganka and F1 Mace stood out for large-fruited. More than 30 mg / 100 g was contained in F1 Izmail F1 Ochakov, F1 Mariachi, F1 Kokhava vitamin C fruits. The nitrate content in tomato fruits was not high for years of research, it was within the MPC.